Analisis Penggunaan Quizizz sebagai Media Pembelajaran untuk Meningkatkan Daya Tarik Belajar Siswa - Hikmah, Laeli Mualinda; Nuroso, Harto; Poncowati, Lilik; Purnamasari, Iin (JURNAL PENA EDUKASI, 2025)
Abstract: One of the main challenges teachers face is a lack of student interest during the learning process, especially in science subjects in elementary school. To address this challenge, this study seeks to analyse the effectiveness of using Quizizz as an interactive learning medium in increasing students' interest in learning. This study uses a qualitative descriptive approach involving 26 fifth-grade students at SDN Wonotingal Elementary School in Semarang. Data were collected through observation, documentation, questionnaires, and formative tests, then analysed descriptively, emphasising patterns of change in student activities and learning outcomes. The findings show that Quizizz can significantly increase student participation. The questionnaire results reinforced this finding with an average score of 4.34 (very high category). In addition, the average score of the students' formative tests also increased, indicating improved learning outcomes. This study confirms that Quizizz is a technology-based entertainment medium that effectively increases students' interest, activity, and academic achievement. The implication of this study is the importance of teachers being more creative in utilising digital media to create interactive, enjoyable, and meaningful learning experiences for students.Keywords: learning appeal; learning media; student learning outcomes; Quizizz.      Abstrak: Salah satu tantangan utama yang dihadapi guru adalah kurangnya minat siswa ketika proses pembelajaran berlangsung, terutama pada mata pelajaran IPAS di sekolah dasar. Untuk menjawab tantangan tersebut, penelitian ini berupaya menganalisis efektivitas penggunaan Quizizz sebagai media pembelajaran interaktif dalam meningkatkan daya tarik belajar siswa. Penelitian ini menggunakan pendekatan deskriptif kualitatif dengan melibatkan 26 siswa kelas V SDN Wonotingal Kota Semarang. Data dikumpulkan melalui observasi, dokumentasi, kuesioner, serta tes formatif, kemudian dianalisis secara deskriptif dengan menekankan pada pola perubahan aktivitas dan hasil belajar siswa. Temuan penelitian menunjukkan bahwa Quizizz mampu meningkatkan partisipasi siswa secara signifikan. Hasil kuesioner memperkuat temuan ini dengan skor rata-rata 4,34 (kategori sangat tinggi). Selain itu, nilai rata-rata tes formatif siswa juga meningkat, yang menandakan adanya perbaikan pada hasil belajar. Secara keseluruhan, penelitian ini menegaskan bahwa Quizizz tidak hanya berfungsi sebagai media hiburan berbasis teknologi, tetapi juga efektif dalam meningkatkan minat, keaktifan, dan capaian akademik siswa. Implikasi dari penelitian ini adalah pentingnya guru untuk lebih kreatif memanfaatkan media digital dalam menciptakan pembelajaran yang interaktif, menyenangkan, sekaligus bermakna bagi peserta didik.Kata kunci: daya tarik belajar; hasil belajar siswa; media pembelajaran; Quizizz.